POTENSI PENGEMBANGAN GASIFIKASI BATUBARA BAWAH PERMUKAAN DI DAERAH ASAM-ASAM, KABUPATEN TANAH LAUT, KALIMANTAN SELATAN: DEVELOPMENT POTENTIAL OF UNDERGROUND COAL GASIFICATION IN ASAM-ASAM AREA, TANAH LAUT REGENCY, SOUTH KALIMANTAN - Muhammad Iqbal Ardiansyah; Ahmad Helman Hamdani; Nurdrajat (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2025)
The potential of underground coal resources in Indonesia has not been fully exploited yet, necessitating new mining methods, one of which is underground coal gasification (UCG). The Asam-asam Basin is one of Indonesia's coal-producing basins that warrants further research regarding the potential development of UCG in the area. This study identifies the geological criteria of coal seams, such as seam thickness, depth, rank, seam dip, surrounding rock types, geological structure, and coal inventory located in the Asam-asam area.Data were collected through core drilling and well logging analysis at 4 boreholes (MIA004–MIA007). The results indicate that the area contains 9 coal seams: A, B, C, D, E, F, G, H, and I. Coal seam thickness varies from 0.49 meter to 18.95 meters, with surrounding rocks predominantly consisting of claystone, and some seams interbedded by sandstone and siltstone. The coal rank is primarily high volatile bituminous. Seams B, C, F, G, and H meet the coal inventory criteria. Evaluation using analytical hierarchy process (AHP) method indicates that Seam F has the highest potential for UCG development, with an average score of 0.78.